Frontmatter (front cover, editorial team, table of contents) - Mohamamd Rofiuddin (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Negeri (IAIN) Salatiga, 2019)
Frontmatter of Indonesian Journal of Islamic Economics Research Vol 1 No 1, 2019